TANGGGUNG JAWAB HUKUM PROVIDER TERHADAP KERUGIAN NASABAH - Wulansari, Febilita; Sukmawati, Ita (Lembaga Marwah Rakyat, 2023)
Indonesia is experiencing very rapid technological developments that are changing the order of human life to become more innovative. The existence of an electronic payment system is one way that people can make cashless transactions. With the emergence of electronic wallets such as DANA, people can carry out many transactions practically, such as paying bills, purchasing goods and services, transferring funds and much more. This research aims to determine the provider's legal responsibility for customer losses on e-wallets. With this research, it is hoped that Bank Indonesia can be more assertive towards providers so that they can take responsibility for losses experienced by customers. This research uses a normative juridical approach. The results state that the provider's responsibility is to provide compensation to customers based on statutory regulations. When making transactions with electronic money, users must feel safe and comfortable so that one of the rights of saving customers is only the right to collect and get the funds back. Other responsibilities are contained in the Electronic Money PBI, Articles 74 and 75 are part of the regulations that regulate sanctions or penalties that can be imposed by Bank Indonesia or other authorities if there is a violation of these regulations. With legal protection, it is hoped that electronic money service providers will better comply with applicable regulations, and consumers will have legal means to protect their rights when using these services